Cell proliferation assay and sulphated glycosaminoglycan production in poly(lactic-co-glycolic acid)-based scaffolds seeded with bone marrow mesenchymal stem cells for cartilage tissue engineering - Abdul Rahman, Rozlin; A. M., Noradibah; Azeman, Nor Athirah; Mohamad Sukri, Norhamiza; Md Nazir, Norhidayah; Ahmad Radzi, Muhammad Aa'zamuddin; Mohamad, Mohd Yusof; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin; Abdul Rahman, Suzanah; Sha'ban, Munirah (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
Articular cartilage tissue is known to have poor capability of self-repair. Therefore, tissue engineering has significantly emerged as an alternative solution for articular cartilage restoration. Poly(lactic-co-glycolic acid) (PLGA) and fibrin have been widely used as biocompatible scaffolds materials to regenerate tissue. In this study, bone marrow mesenchymal stem cells (BMMSCs) were seeded onto the PLGA with (PLGA/Fibrin) or without fibrin (PLGA only). Macroscopic observation, MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) and sulphated glycosaminoglycan (sGAG) assays were performed at week 1, 2 and 3 in vitro. Both PLGA/Fibrin and PLGA only groups showed similar hyaline-like appearance with white and smooth glistening surface. The MTT assay showed higher cell proliferation in the PLGA/Fibrin than the PLGA only group. The production of sGAG is higher in the PLGA/Fibrin group than in the PLGA only. This may suggest that PLGA/Fibrin may serve as prospective cell delivery vehicle and essential foundation for in vitro tissue engineered articular cartilage.